Teacher’s health and presenteeism - Garcia, Tatiana Varejão [UNESP]; Juliani, Carmen Maria C.M. [UNESP] (EDITORA SCIENTIFIC, 2024)
Presenteeism is a relatively new phenomenon affecting the health of employees, and studies on this topic are scarce. It refers to being physically present in the workplace but mentally or physically unable to fully perform one’s duties. For teachers in particular, this is influenced by internal and external factors that determine their relationship with work. The objective of this study was to understand how presenteeism developed among teachers from a school in the city of São Paulo, Brazil, which offers secondary education programs including basic professional and technical qualification. This was a qualitative study using Bardin’s content analysis method. Twenty teachers suffering from presenteeism were randomly selected to compose the purposive sample. Data were collected from September to December 2019. Participants complaints were mainly related to school organization and their own relationship with work. Several factors lead to illness and impact teachers’ health and quality of life, such as physical and emotional exhaustion, difficulties in recovering health, suffering, underperformance, difficulty taking sick leaves, and professional and financial damages. Presenteeism involves personal, financial, and sociocultural issues, as well as organizational factors that make teachers feel obligated to work even when they are sick to perform their duties.
Saúde dos professores e o presenteísmo
Keywords: occupational health; presenteeism; school teachers